Penghambatan Pertumbuhan Jamur Fusarium oxysporum Schlecht Pada Batang Padi (Oryza sativa L.) Menggunakan Ekstrak Metanol Umbi Bawang Mekah (Eleutherine palmifolia Merr.) - Mukarlina, Nuryanti Diana, Siti Khotimah, (Jurnal Protobiont, 2014)
The wilt disease caused by  Fusarium oxysporum  Schlecht is a constraint in the cultivation of rice (Oryza sativa  L.).  This  study aim  was  to  determine  the  potential  of  the  methanol extract of  mekah  onion (Eleutherine palmifolia  Merr.) bulbs as antifungal for  F. oxysporum. The fungi was isolated from rice stem samples that showed symptoms of  Fusarium  wilt disease. Fungi isolation was done through direct planting method and the test of antifungal inhibition capability was done by solid dilution method through poisoning food. The test results showed that the methanol extract of mekah onion bulbs contain secondary metabolites are able to inhibit the growth of of  F. oxysporum colonies. Concentration of 62.5% has significant effect on inhibiting the  growth of F. oxysporum.